2021
DOI: 10.3390/healthcare9111479
|View full text |Cite
|
Sign up to set email alerts
|

Out of the Closet, Not Yet Out of the House: Gay Men’s Experiences of Homonegativity and Internalized Homonegativity

Abstract: This paper explores how Australian gay men experience gender and sexuality in relation to heteronormative gender norms, specifically masculinity. A sample of 32 gay men 22–72 years of age participated in an online interview, using a videoconferencing software, on masculinity and homosexuality. Thematic analyses revealed that gay men experience gender and sexuality-related strain across all levels of their socioecological environment through social regulation, homophobic discrimination/harassment, and anti-effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Indeed, there is currently a developing interest from different research groups involved in research in healthcare experiences for sexual and gender minority people. Various researchers have focused on these LGBT populations using a variety of different types of studies, such as audits [ 57 ], observational studies [ 58 ], qualitative research [ 59 ], mixed-methods designs [ 60 ], and a current protocol for a systematic review [ 61 ], to monitor the improvement in health, well-being, and healthcare experiences for sexual and gender minority people. This research is likely to contribute to the better understanding of any issues as well as further opportunities to address them.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there is currently a developing interest from different research groups involved in research in healthcare experiences for sexual and gender minority people. Various researchers have focused on these LGBT populations using a variety of different types of studies, such as audits [ 57 ], observational studies [ 58 ], qualitative research [ 59 ], mixed-methods designs [ 60 ], and a current protocol for a systematic review [ 61 ], to monitor the improvement in health, well-being, and healthcare experiences for sexual and gender minority people. This research is likely to contribute to the better understanding of any issues as well as further opportunities to address them.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, “society pressures gay men to negotiate who they are according to hegemonic masculinity to compensate for their same-sex sexual preference” (Eguchi, 2009, p. 194), which situates a gendered power struggle at the core of gay male identity. This internalized heteronormative masculinity, and its subsequent rules, then leads individuals to regulate the behavior of both themselves and other gay men (Thepsourinthone et al, 2021), as evidenced by the discourses produced on these groups.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…The term "homonegativity" refers to negative reactions or attitudes towards homosexuality [1]. Assessing the levels and determinants of homonegativity within societies is crucial, as numerous studies have indicated its severe impact on the health and well-being of homosexuals [2][3][4]. For instance, homosexuals who face homonegativity often grapple with feelings of shame and self-loathing, leading to isolation [2], depression, anxiety, poor mental health [3], as well as alcohol abuse and even suicide [4].…”
Section: Introductionmentioning
confidence: 99%
“…Assessing the levels and determinants of homonegativity within societies is crucial, as numerous studies have indicated its severe impact on the health and well-being of homosexuals [2][3][4]. For instance, homosexuals who face homonegativity often grapple with feelings of shame and self-loathing, leading to isolation [2], depression, anxiety, poor mental health [3], as well as alcohol abuse and even suicide [4]. Given the profound consequences of homonegativity on the well-being of homosexuals, it is imperative to understand its determinants.…”
Section: Introductionmentioning
confidence: 99%